2021
DOI: 10.4997/jrcpe.2021.218
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Simulation via Instant Messaging – Birmingham Advance (Simba) in Medical Education during Covid-19 Pandemic

Abstract: Background Simulation via Instant Messaging - Birmingham Advance (SIMBA) aimed to improve clinicians’ confidence in managing various clinical scenarios during the COVID-19 pandemic. Methods Five SIMBA sessions were conducted between May and August 2020. Each session included simulation of scenarios and interactive discussion. Participants’ self-reported confidence, acceptance, and relevance of the simulated cases were measured. Results Significant improvement was observed in participants’ self-reported con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…From the 92 published studies, VS was reported to be applied in the educational practice involving undergraduate medical students across 25 countries including the United States [26 studies ( 15 40 )], the United Kingdom [9 studies ( 41 49 )], Germany [7 studies ( 50 – 56 )], China [6 studies ( 10 , 57 61 )], Denmark [6 studies ( 62 – 67 )], France [4 studies ( 68 71 )], Japan [4 studies ( 72 75 )], Sweden [3 studies ( 76 78 )], Canada [3 studies ( 79 – 81 )], Netherlands [3 studies ( 82 84 )], Spain [3 studies ( 85 87 )], Australia [2 studies ( 88 , 89 )], Singapore [2 studies ( 90 , 91 )], Korea [2 studies ( 92 , 93 )], Finland [1 study ( 94 )], Italy [1 study ( 95 )], Ireland [1 study ( 96 )], Colombia [1 study ( 97 )], Pakistan [1 study ( 98 )], Thailand [1 study ( 99 )], Iran [1 study ( 100 )], Poland [1 study ( 101 )], Mexico [1 study ( 102 )], Norway [1 study ( 103 )], Saudi Arabia [1 study ( 104 )], and Switzerland [1 study ( 105 )]. The distribution of included studies among different continents was shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From the 92 published studies, VS was reported to be applied in the educational practice involving undergraduate medical students across 25 countries including the United States [26 studies ( 15 40 )], the United Kingdom [9 studies ( 41 49 )], Germany [7 studies ( 50 – 56 )], China [6 studies ( 10 , 57 61 )], Denmark [6 studies ( 62 – 67 )], France [4 studies ( 68 71 )], Japan [4 studies ( 72 75 )], Sweden [3 studies ( 76 78 )], Canada [3 studies ( 79 – 81 )], Netherlands [3 studies ( 82 84 )], Spain [3 studies ( 85 87 )], Australia [2 studies ( 88 , 89 )], Singapore [2 studies ( 90 , 91 )], Korea [2 studies ( 92 , 93 )], Finland [1 study ( 94 )], Italy [1 study ( 95 )], Ireland [1 study ( 96 )], Colombia [1 study ( 97 )], Pakistan [1 study ( 98 )], Thailand [1 study ( 99 )], Iran [1 study ( 100 )], Poland [1 study ( 101 )], Mexico [1 study ( 102 )], Norway [1 study ( 103 )], Saudi Arabia [1 study ( 104 )], and Switzerland [1 study ( 105 )]. The distribution of included studies among different continents was shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the above learning contexts and practical aspects, the remaining 18 articles ( 15 , 21 , 24 , 27 , 40 , 41 , 43 , 54 , 73 , 77 , 83 , 87 , 89 , 95 , 100 , 102 , 103 , 105 ) reported the integration of VS into other case-based learning experiences in virtual patient-care settings. Despite the diversity of virtual patient systems and clinical scenarios, these studies generally showed that VS-integrated case-based learning as a feasible teaching approach ( 54 ) could result in students’ learning gains, retention of information, and transfer of knowledge to clinical application ( 89 , 95 , 100 , 102 ), help future physicians improve diagnostic accuracy thus enhance the clinical reasoning teaching ( 15 , 27 , 43 ), extend students’ preparedness level for their future clinical experiences ( 40 , 83 ), facilitate empathy ( 24 ), cultural competence ( 77 ) and comprehensive clinical skills such as communication-based skills ( 21 ), clinical decision-making skills ( 78 ) within undergraduate medical education, and improve students’ confidence in managing clinical scenarios ( 41 ), thus was highly received by students ( 89 , 95 , 105 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…SIMBA was initially conceptualised in July 2019 as a minimal-cost simulation-based programme delivered through WhatsApp, which has proved highly effective in improving learners’ self-reported confidence in managing endocrinology and diabetes cases 5. It has since branched into other specialties, including gastroenterology, hepatology and paediatrics, with plans to expand further 6. With the onset of the COVID-19 pandemic and the unprecedented disruptions to health professions education, we expanded SIMBA on an international scale as our response to the disruption to medical education and training in acute medicine.…”
Section: Introductionmentioning
confidence: 99%